1986
DOI: 10.1007/bf00263819
|View full text |Cite
|
Sign up to set email alerts
|

Tumor imaging with carbon-11 labeled alpha-aminoisobutyric acid (AIB) in a patient with advanced malignant melanoma

Abstract: A 29 year-old-man presenting with advanced metastatic malignant melanoma was successfully imaged using carbon-11 (11C) labeled alpha-aminoisobutyric acid (AIB), a synthetic, non-metabolized amino acid transported into viable cells by the A-type, or alanine-preferring, amino acid transport system. Tumor located in the hilum of the lung was well visualized with 11C-AIB prior to chemotherapy. A gallium image with liver subtraction using 99mTc-sulfur colloid demonstrated regions of increased activity in liver whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…In these studies, AIB generally demonstrated good tumor imaging properties, although the uptake in the spontaneous canine tumors was variable. PET studies performed with [ 11 C]AIB in a small number of patients with melanoma demonstrated increased uptake in tumor relative to normal tissues in most but not all of the melanoma tumors . Similarly, in two patients with soft tissue sarcomas, [ 11 C]AIB demonstrated good tumor visualization .…”
Section: Fluorine‐18 and Radioiodinated αα‐Dialkyl Amino Acidsmentioning
confidence: 94%
See 1 more Smart Citation
“…In these studies, AIB generally demonstrated good tumor imaging properties, although the uptake in the spontaneous canine tumors was variable. PET studies performed with [ 11 C]AIB in a small number of patients with melanoma demonstrated increased uptake in tumor relative to normal tissues in most but not all of the melanoma tumors . Similarly, in two patients with soft tissue sarcomas, [ 11 C]AIB demonstrated good tumor visualization .…”
Section: Fluorine‐18 and Radioiodinated αα‐Dialkyl Amino Acidsmentioning
confidence: 94%
“…To date, the majority of radiolabeled amino acids for tumor imaging target system L transporters, and many of these tracers are derivatives of the natural amino acids L ‐phenylalanine and L ‐tyrosine, including L ‐3‐[ 123 I]iodo‐α‐methyl tyrosine (IMT), O ‐(2‐[ 18 F]fluoroethyl)‐ L ‐tyrosine (FET), and L ‐3,4‐dihydroxy‐6‐[ 18 F]fluorophenylalanine (FDOPA) . To a lesser extent, radiolabeled amino acids targeting system A amino acid transport, such as α‐aminoisobutyric acid (AIB) and its N ‐methyl analog MeAIB have been evaluated for tumor imaging …”
Section: Introductionmentioning
confidence: 99%
“…Initial studies with radiolabeled AIB in animals including murine melanoma xenograft and canine spontaneous tumor models demonstrated uptake in some but not all tumors [187,188]. Studies of [ 11 C]AIB in a small number of patients with soft tissue sarcomas and melanoma showed good uptake in the majority of the known tumors [177,178,189]. The high degree of regulation of system A transport by factors such as amino acid availability [51,[63][64][65]190] has been proposed as a major source of this observed variability.…”
Section: αα-Dialkyl Amino Acidsmentioning
confidence: 96%
“…The syn-and anti-3-IVACBC and gem-3-IVACBC stannylated precursors (68)(69)(70) were obtained from the corresponding iodo-derivatives (56,57,59), respectively, as shown in Scheme 14. 47 There are several advantages to using organotin precursors.…”
Section: Synthesis Of the Iodine-123 Alicyclic Amino Acidsmentioning
confidence: 99%
“…For use in PET studies, AIB has been labeled with carbon-11 at the carboxylic acid position ([1-11 C]AIB), [52][53][54][55][56] at the α-carbon position ([2-11 C]AIB), 57,58 and at the αmethyl position ([3-11 C]AIB). 59,60 Similarly, MeAIB has been labeled at the α-carbon position ([2-11 C]MeAIB) 57 and at the N-methyl position ([N-methyl-11 C]MeAIB). 61 Preliminary evaluation of [2-11 C]AIB and [N-methyl- 11 C] MeAIB has shown promise for PET tumor imaging in patients with chest and other malignancies.…”
Section: Synthesis Of the Iodine-123 Alicyclic Amino Acidsmentioning
confidence: 99%